MEDIA. MEDIALITY. IMAGE – MEDIA-PHILOSOPHICAL INVESTIGATION IN THE IMAGE-RESEARCH - FÁM, Erika (Studia Universitatis Babeș-Bolyai Philosophia, 2017)
Media. Mediality. Image. Media-Philosophical Investigation in the Image-Research. The concept of the media has been redefined many times; the medial interpretation of postmediality is only a critique of existing media-approaches and actuality. The concept of media is hardly going to disappear, its use has become increasingly popular, and the range of interpretation has become wider, the Media Studies brings together more and more sciences; it is not a limit science, but a cumulative science. In W. J.T. Mitchell’s approach, the media is more than a medium, the media is a relation, there is no pure media, and all media are mixed. Breaking down the idea of the mixed media, we could make parallels/contrasts between the concept of total mediality and the concept of postmediality. Postmediality sees a way in the passing by overtaking of the concept of media (Manovich) in aesthetics, visual theory, art theory, media theory, but perhaps most of all the media concept should be sought as it is, just a different type of media use which has become commonplace in the digital-galaxy. Totalmediality is trying to point out the use of new media, and beyond this to the open media borders, overlappings, while the media is not just carrier material but also form. The study treats totalmediality as theoretical possibility for overcoming postmediality in Mitchell’s interpretation of media and emphasizing the dominance of visuality in the media-applications.